2014
DOI: 10.1016/j.amjsurg.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo leukocyte-mediated brain microcirculatory inflammation: a comparison of osmotherapies and progesterone in severe traumatic brain injury

Abstract: BACKGROUND Mannitol, hypertonic saline, and progesterone may blunt leukocyte recruitment after traumatic brain injury (TBI). We hypothesized that progesterone reduces pericontusional recruitment of leukocytes to a greater extent than either osmotherapy a day after TBI. METHODS CD1 mice underwent controlled cortical impact and were treated with osmotherapy (mannitol and hypertonic saline) or progesterone. Thirty-two hours after TBI, live pial microscopy was used to evaluate leukocyte–endothelial interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…While LEU rolling is an important step in LEU/EC interactions leading to transmigration into the tissue phase, in the current study, the number of sticking or adherent LEUs was extremely low as we could only safely record 30 seconds of fluorescent exposure at a time to prevent fluorescent light effects on the pial surface. 21,26,47 We can only postulate that differences could not be ascertained with such low frequency of adhesion. It is important to note that other plausible explanations may also exist linking heparinoids to reduced LEU rolling.…”
Section: Discussionmentioning
confidence: 94%
“…While LEU rolling is an important step in LEU/EC interactions leading to transmigration into the tissue phase, in the current study, the number of sticking or adherent LEUs was extremely low as we could only safely record 30 seconds of fluorescent exposure at a time to prevent fluorescent light effects on the pial surface. 21,26,47 We can only postulate that differences could not be ascertained with such low frequency of adhesion. It is important to note that other plausible explanations may also exist linking heparinoids to reduced LEU rolling.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, in a study using the CCI method in 4 week old mice, progesterone treatment only improved wire grip scores in male mice, but worsened performance in females (Mannix et al, 2014), suggesting that the hormonal status prior to injury could influence whether progesterone treatment is beneficial or not. General neurological function, measured with the modified Neurological Severity Score (mNSS), can likewise be improved with progesterone treatment following a TBI in rats (Li et al, 2012; Pan et al, 2007), or mice (Kumasaka et al, 2014) independent of the injury model used. Classical psychiatric problems, like anxiety, also seem to be affected by progesterone treatment, since progesterone reduces anxiety levels after a weight-drop TBI in male and female rats in the EPM (Baykara et al, 2013).…”
Section: Sex Differences In Animal Models Of Tbimentioning
confidence: 99%
“…Data from preclinical experiments in animal models have demonstrated that hyperosmolar therapy reduced leukocyte recruitment at the lesion site after TBI [90]. Models of intracerebral hemorrhage and cerebral ischemia have demonstrated that HTS and mannitol may reduce pro-inflammatory mediators and pro-inflammatory microglia activation and, thereby, attenuate neuroinflammation and cerebral edema [91][92][93][94].…”
Section: Hyperosmolar Therapymentioning
confidence: 99%